Assessing Virus Survival in African Swine Fever Virus-Contaminated Materials—Implications for Indirect Virus Transmission - Christina Marie Lazov; Ann Sofie Olesen; Graham J. Belsham; Anette Bøtner (Viruses)
Introduction of African swine fever virus (ASFV) into pig herds can occur via virus-contaminated feed or other objects. Knowledge about ASFV survival in different matrices and under different conditions is required to understand indirect virus transmission. Maintenance of ASFV infectivity can occur for extended periods outside pigs. Current assays detecting ASFV have inherent disadvantages. Cell culture-based assays are labor-intensive and sensitive to contaminants while methods using qPCR detect ASFV DNA with high sensitivity and specificity, but this may not correspond to infectious virus. Here, we have combined the use of these assays to assess the replication of ASFV within cells and determined the effect of pig feces, straw, wood shavings, and mixed feed on ASFV infectivity. In porcine serum, infectious ASFV survived for at least 60 days at 4 °C, 22 °C, and 37 °C; for two days at 50 °C; one day at 60 °C; and ≤5 min at 70 °C. In the presence of feed, straw, or wood shavings, the survival of the virus wasmarkedly shortened. Samples remained positive in the qPCR assay despite the loss of virus infectivity. Thus, it was possible to distinguish between the presence of ASFV DNA and the survival of the infectious virus.